Unsur Tasawuf dalam Perupaan Wayang Kulit Purwa Cirebon dan Surakarta - Moh. Isa Pramana; Yustiono Yustiono; Wisoyo Yudoseputro (Journal of Visual Art and Design, 2007)
Wayang Kulit Purwa"”based on Indian epics and original Javanese myths"”is considered as the media link between the Hindi-Buddhism era (Kabudan) and the Islamic era (Kewalen) of the Indonesian traditional arts. It is assumed that wayang kulit holds a relationship role to these two eras. The effort to understand this relationship can only be explained through Sufism that was practiced by the Nine Apostles of Java (Wali Sanga) who has contributed a great deal to the Wayang Kulit Purwa adaptations. It is obvious that there are Sufistic meanings in the visualizations of the figure in Wayang Kulit Purwa as shown by differences of dimensions and intensities in its manifestations, even with the same local area (gagrak). Differences are range from visual details among different figure appearances of the similar character, called wanda, to the different figure appearances of different characters. This is particularly more obvious in the differences between the gagrak of Cirebon and Surakarta. This study focuses on the analysis of various characters figures such Bima, Mintaraga, Semar, Cakil, Rahwana, Duryudhana and Dursasana from both gagraks of wayang kulit. The Cirebon gagrak shows a Sufistic understanding which looks to the medium not in a serious matter, being more straight forward, more egalitarian and more focused. On the other hand, Surakarta gagrak shows a Javanese Sufistic understanding that put the importance of visualizing elegance and grace-ness in manners and spirituality, as a proof of harmony between the world of physique and spirituality.